A rare case report of Sertoli Leydig cell tumour of ovary - Rita D.; Ravali G. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Sertoli-Leydig cell tumor (SLCTs) of the ovary, also known as androblastoma, is a rare neoplasm from the group of sex cord-stromal tumors of the ovary. They account for less than 0.5% of all ovarian tumors. They typically occur in young and reproductive women and the patients usually present with abdominal swelling or pain. A case of 35-year-old multiparous female presented with abdominal mass, ultrasonography revealed a large abdomino-pelvic complex solid cystic mass lesion arising from left ovary. She underwent staging laparotomy followed by total abdominal hysterectomy with left salpingo-ovariotomy and right salpingo-oopherectomy with partial omentectomy. Histopathological examination (HPE) revealed features suggestive of moderately differentiated SLCT of left ovary (with heterologous elements).